Oxidoreductase - Ahmed Mansour, Mahmoud (Biochemistry, 2021)
Oxidoreductase enzymes are a group of enzymes that catalyzes the transfer of electrons from one molecule, the reductant, also called the electron donor, to another, the oxidant, also called the electron acceptor. Oxidoreductase enzymes utilize NADP+ or NAD+ as cofactors. Oxidoreductase enzymes include the following: oxidase, dehydrogenase, peroxidase, hydroxylase, oxygenase, and reductase. Most oxidoreductase enzymes are dehydrogenases. However, reductases are also common. The accepted nomenclature for dehydrogenases is "donor dehydrogenase", where the donor is the oxidized substrate. Metabolic abnormalities disorders resulting from a deficiency (quantitative and qualitative) or from over-activity of oxidoreductase, which may contribute to the decreased normal performance of life, are becoming common. This book covers the potential applications of oxidoreductases on the growth of oxidoreductase-based diagnostic tests and better biosensors in the design of inventive systems for crucial co-enzyme generations and in the synthesis of polymers and organic substrates. The book describes the role of oxidoreductase as essential in medical drug formation. It can be employed to produce a huge amount of compounds that act as medical mediators like Cephalosporin (beta lactam antibiotic). Furthermore, the idea of how to use different enzymes as targets for medical treatment in different types of cancers is also described in this book.